(untitled) (Biological Sciences - PJSIR, 2008)
. For determining the chemical composition of seabuckthorn oil of different origins, samples of seabuckthorn berries (red and yellow varieties) were collected from different locations of northern areas of Pakistan. Among eight different fatty acids, palmitoleic acid (32.4%) and palmitic acid (36.52 %) were found to be the major fatty acids present along with other important fatty acids i.e., oleic acid (37.07%), linoleic acid (12.36%) and linolenic acid (0.73%). Quantities of unsaturated fatty acids were higher than that of saturated analogues.